2016
DOI: 10.1016/j.autrev.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of B cells and autoantibodies in neuropsychiatric lupus

Abstract: The central nervous system manifestations of SLE (neuropsychiatric lupus, NPSLE) occur frequently, though are often difficult to diagnose and treat. Symptoms of NPSLE can be quite diverse, including chronic cognitive and emotional manifestations, as well as acute presentations, such as stroke and seizures. Although the pathogenesis of NPSLE has yet to be well characterized, B-cell mediated damage is believed to be an important contributor. B-cells and autoantibodies may traverse the BBB, promoting an inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Although the precise mechanism underlying each individual type of end-organ pathology in lupus has yet to be fully elucidated, autoantibody deposition is thought to be important in both types of tissue [ 5 , 21 ]. Other potential contributions of B cells to the mechanisms of target organ injury in lupus are antigen presentation and cytokine secretion [ 22 ]. Furthermore, we have previously shown that macrophages are important for the development of both spontaneous and ultraviolet B irradiation-induced skin lesions in lupus mice and in the pathogenesis of murine NPSLE [ 7 – 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism underlying each individual type of end-organ pathology in lupus has yet to be fully elucidated, autoantibody deposition is thought to be important in both types of tissue [ 5 , 21 ]. Other potential contributions of B cells to the mechanisms of target organ injury in lupus are antigen presentation and cytokine secretion [ 22 ]. Furthermore, we have previously shown that macrophages are important for the development of both spontaneous and ultraviolet B irradiation-induced skin lesions in lupus mice and in the pathogenesis of murine NPSLE [ 7 – 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…During an inflammatory episode, perivascular accumulation of mononuclear cells and cytokines either in the systemic circulation or CNS may disrupt the blood brain barrier, allowing the passage of autoantibodies into the CNS [29,30]. Autoantibody deposition leads to neurotoxicity and glial cell activation, thereby producing an abundance of cytokines in the CNS and perturbing normal neuronal function.…”
Section: Proposed Mechanisms Of Npslementioning
confidence: 99%
“…A review article by Wen et al [ 21 ] states the role of B cells in the adverse behavioral symptoms in NPSLE as it crosses the blood-brain barrier and causes glial activation and neurodegeneration [ 21 ]. Improper regulation of cytokines IFN-α, tumor necrosis factor (TNF), and IL-6 may cause disruption of the BBB, and also the elevated levels of cytokines within the CNS such as TNF-like weak inducer of apoptosis (TWEAK) may be responsible for some of the neuropsychiatric changes in lupus [ 22 , 23 ].…”
Section: Reviewmentioning
confidence: 99%